25-Hydroxy cholecalciferol, anti-Müllerian hormone, and thyroid profiles among infertile men. (9th April 2021) - Hassan, Mohammed H.; Ibrahim, Hassan M.; El-Taieb, Moustafa A.
Abstract: Background and aim: We examined the relationship among vit.D3, AMH, FT3, FT4, and TSH, in addition to the serum levels of reproductive hormones (FSH, LH, prolactin, and free testosterone), in oligoasthenoteratozoospermia and azoospermia patients in a cohort of infertile men from Egypt to establish a clinical marker/cause-effect relationship. Methods: This cross-sectional cohort study was carried out on 301 men (105 males with oligoasthenoteratozoospermia and 96 males with azoospermia), in addition to 100 controls. Measurements of serum vit.D3, AMH, FT3, FT4, and TSH levels, in addition to reproductive hormone assays, were performed on all included subjects, using ELISA kits. Results: Overall, results showed significantly lower serum levels of vit.D3 in infertile men than in the controls, with a greater decrease observed in men with azoospermia than in oligoasthenoteratozoospermia patients, ( p < .05 for all). Significantly higher serum TSH and FSH levels and significantly lower serum free testosterone levels were observed in males with azoospermia than in males with oligoasthenoteratozoospermia and the controls ( p < .05 for both). There were no significant differences between the studied groups in terms of AMH, FT3 or FT4 levels. LH levels were negatively correlated with TSH levels and positively correlated with AMH levels among men with oligoasthenoteratozoospermia, while among men with azoospermia, LH levels were positively correlated with vit.D3 levels ( p < .05 for all). Conclusion: Decreased Vit.D3 could play a role in male infertility, in addition to abnormal thyroid function, which needs further investigation.